2018
DOI: 10.1002/qua.25727
|View full text |Cite
|
Sign up to set email alerts
|

Fisher information in confined isotropic harmonic oscillator

Abstract: Fisher information (I) is investigated in a confined harmonic oscillator (CHO) enclosed in a spherical enclosure, in conjugate r and p spaces. A comparative study between CHO and a free quantum particle in spherical box (PISB), as well as CHO and respective free harmonic oscillator (FHO) is pursued with respect to energy spectrum and I. This reveals that, a CHO offers two exactly solvable limits, namely, a PISB and an FHO. Moreover, the dependence of I on quantum numbers n r, l, m in FHO and CHO are analogous… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 58 publications
(111 reference statements)
0
29
0
Order By: Relevance
“…The DVR methods, on the contrary, are quite suitable to deal with such confined systems because the discretization of a finite domain is much easier than an infinite one. The application of the GPS method to various confined atoms have been well demonstrated by Roy et al, [ 40–45 ] and the efficiencies and powerfulness of such a method have been revealed. Interestingly, however, it was found that, when calculating the radial expectation values for confined atoms, the powerful GPS method shows significant discrepancies with other state‐of‐the‐art methods.…”
Section: Introductionmentioning
confidence: 99%
“…The DVR methods, on the contrary, are quite suitable to deal with such confined systems because the discretization of a finite domain is much easier than an infinite one. The application of the GPS method to various confined atoms have been well demonstrated by Roy et al, [ 40–45 ] and the efficiencies and powerfulness of such a method have been revealed. Interestingly, however, it was found that, when calculating the radial expectation values for confined atoms, the powerful GPS method shows significant discrepancies with other state‐of‐the‐art methods.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, intense theoretical studies on information‐theoretical measures for different quantum systems have been performed. In this way, different potential profiles in the Schrödinger equation have been assumed, for example, Dirac‐delta‐like potentials, hyperbolical potential, power‐type potentials, D ‐dimensional harmonic oscillator and hydrogen atom, for Morse and Pöschl‐Teller potentials, the Rydberg‐like harmonic states, infinite potential well, double square well potential, infinite circular and spherical wells, an electron in one‐dimensional nonuniform systems, one‐dimensional Anderson model, two‐electron atoms, hydrogen atom under soft spherical confinement, the information‐entropic measures in free and confined hydrogen atom, information entropy for Eckart potential, modified Hylleraas plus exponential Rosen‐Morse potential, a squared tangent potential well, a parity‐restricted harmonic oscillator, the Fisher entropy for infinite circular and spherical wells, and so on. The quantum information theory plays an important role in the measurement of uncertainty and other related parameters of an assumed quantum system.…”
Section: Introductionmentioning
confidence: 99%
“…Most efforts have been centered around the spectroscopic properties and some density‐functional descriptors of physical and chemical quantities for the ground state of spherically confined atoms . However, not so much is known about the information‐theoretical measures of the multidimensional confined systems except for a few recent entropy‐like and complexity‐like results of the three‐dimensional confined hydrogenic atom. The aim of this work is to cover this lack of information by determining the confinement dependence of some entropy (Shannon, Fisher) and complexity (Fisher‐Shannon, lopezruiz‐mancini‐alvet (LMC) and LMC‐Rényi) measures for the 1s, 2s, 2p, and 3d quantum states of the two‐dimensional confined hydrogenic atom (2D‐CHA, in short) in both position and momentum spaces.…”
Section: Introductionmentioning
confidence: 99%